Exact results for a special PT-symmetric optical potential - Jones,HF (Springer, 2019)
We present exact analytical results for the sinusoidal optical potentialsυ(x) ∝ cosKx + iλ sinKx, particularly for the special case λ = 1. This is at the borderline between broken and unbroken PT symmetry, and propagation through such an optical lattice exhibits many remarkable properties.